Agile oracle application express - Cimolini, Patrick (Apress, 2012)
Agile Oracle Application Express shows how skilled, motivated, and self-organizing developers can realize extraordinary commercial benefits from Oracle Application Express. The secret is to couple Application Express with an agile software development approach. This book leads the way. Oracle Application Express is well-suited to agile processes, with its support for rapid prototyping and team development. Application Express supports a gamut of enabling technologies such as SQL, HTML, CSS, JavaScript, and more that enable you to deliver any type of web application to meet your development needs. Agile Oracle Application Express helps you take the feature set of Application Express and marry it with the processes of agile development to iteratively design, create, and deliver quality applications on time and within budget.